Analysis of 2D and 3D GPR data interpretation using continuous wavelet transforms: Case study from an archaeological test site - Iqbal, Ibrar; Xiong, Bin; Tian, Gang; Ali, Amjad; Peng, Sanxi; Wen, Gao; Huang, Xingfu; Anees, Aqsa; Ashraf, Umar; Abd El-Raouf, Amr (Frontiers in Earth Science, 2022)
Ground-penetrating radar (GPR) is one of the most important techniques for obtaining high-resolution data in archaeological research, and it is becoming increasingly important. Continuous wavelet transform (CWT) is a mathematical algorithm that can easily determine the local anomalies in the time series dataset. This paper focuses on the novel technique of integrating CWT and the wavelet transform maxima line (WTMM) to extract information from an archaeological test site in south-eastern China. For the characterization of archaeological features, we assessed the importance of dense and accurate data collection as well as GPR signal processing. The mathematical formulation and applicability of GPR attributes, particularly amplitude-based attributes, to identify and characterize archaeological buried targets are also discussed. GPR data is acquired using co-polarized and cross-polarized configurations with transverse-electric (TE) and trans-verse-magnetic (TM) broadside frequency plates at 100 MHz and 200 MHz. Next, CWT was applied using six different wavelet levels, followed by amplitude comparison. The archaeological targets were successfully interpreted using peak amplitude and CWT. The proposed methodology has significantly improved data visualization and interpretation of GPR data, and it also gave us good results in identifying archaeological anomalies.